Dosimetric characterisation of the nanodot optically stimulated luminescent dosimeter for use in national electron beam dosimetry audit services for radiotherapy facilities - Mohd Noor, Noramaliza; Abdullah, Norhayati; Kamarul Zaman, Z.; Ngie, Min Ung; Mohammad Zahid, M. (Longe Medikal Sdn Bhd, UPM-MTDC Technology Centre, 2024)
The Malaysian Nuclear Agency's secondary standard dosimetry laboratory (SSDL) aims to establish a national dosimetry audit service for radiotherapy facilities. For this purpose, a nanoDot optically stimulated luminescent dosimeter (OSLD) was selected as the transfer dosimeter for the audit program. The study aims to establish the basic dosimetric characteristics and associated correction factors of nanoDot OSLD for use in electron beam dosimetry audits. An investigation of the dosimetric characteristics of the nanoDot, comprising the sensitivity correction factor (SCF), dose-response linearity, beam energy dependency, signal depletion per readout, and signal fading when subjected to electron beams, was conducted. A preliminary electron beam dosimetry audit using nanoDot OSLD was performed for two radiotherapy facilities under both reference and non-reference conditions. The measurement uncertainty of the absorbed dose for the nanoDot OSLD was also estimated. The mean SCF of the 91 nanoDot OSLD was 1.001 ± 0.25%. The dose-response curves for the 6 MeV and 9 MeV beams exhibited linear characteristics, with a determination coefficient of 0.9982 for the dose range of 50–300 cGy. However, a high energy dependency was observed at 12 MeV, resulting in a deviation of 4.08% compared to that at 6 MeV. The nanoDot signal decreased by 0.03% after 100 readouts and faded by 3.20% at 70 days post-irradiation. It is noteworthy that all audit results from the six electron beams were in compliance with the tolerance limit of ± 5%, with mean dose deviations of -1.66% ± 0.81% and -1.37% ± 0.65% for the reference and non-reference conditions, respectively. The combined uncertainty was estimated to be ± 1.41% (coverage factor, k = 1). National electron beam dosimetry audits using nanoDot OSLD can now be implemented as a regular service.